Recent Advances in the Linkers of Drug Conjugates - Deng, Shirui; Wen, Xiaoan; Wang, Jinzheng (Current Medicinal Chemistry, 2025)
Drug conjugates have emerged as a pivotal research focus in the field of targeted cancer therapy. They represent a widely explored prodrug strategy that significantly enhances the therapeutic index of drugs while minimizing side effects. The stability and selective cleavage of the linker within drug conjugates are critical for the therapeutic efficacy and targeted treatment achieved by these conjugates. In this review, we have categorized the linkers based on their cleavage mode and summarized the chemical properties, advantages, and limitations of various types of cleavable linkers. Particularly, examples have been provided to illustrate their specific potential for development.
Keywords: Linkers